2020
DOI: 10.1186/s12889-020-8403-8
|View full text |Cite
|
Sign up to set email alerts
|

Image-and-text health warning labels on alcohol and food: potential effectiveness and acceptability

Abstract: Background: Health warning labels (HWLs) using images and text to depict the negative health consequences of tobacco consumption are effective and acceptable for changing smoking-related outcomes. There is currently limited evidence concerning their potential use for reducing consumption of alcoholic drinks and energy-dense foods. The aim of this research was to describe the potential effectiveness and acceptability of image-and-text (also known as pictorial or graphic) HWLs applied to: i. alcoholic drinks and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 37 publications
9
49
0
Order By: Relevance
“…One paper reported on two studies using different methodologies to study the same variables [50], and four papers reported on different aspects of one intervention [51][52][53][54]. The remaining papers were individual studies (with a complete or partial focus on alcohol HWL labelling), although some of them were part of the same research line of label development and testing (e.g., [55][56][57][58][59][60]) or studied the same labels (e.g., [61,62]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One paper reported on two studies using different methodologies to study the same variables [50], and four papers reported on different aspects of one intervention [51][52][53][54]. The remaining papers were individual studies (with a complete or partial focus on alcohol HWL labelling), although some of them were part of the same research line of label development and testing (e.g., [55][56][57][58][59][60]) or studied the same labels (e.g., [61,62]).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of study aims and studied independent variables, five papers (19%) compared only new or enhanced labels with no or regular labels [51][52][53][54]63]. Focusing on label content, eight papers (30%) compared text-only labels with text and image labels [55,56,61,62,[64][65][66][67], twelve studies (44%) compared text message characteristics (e.g., content, specificity, framing, source, use of causal language) [57][58][59][60][67][68][69][70][71][72][73][74] and three (11%) compared image characteristics [57,66,75]. Four (15%) papers compared label formats, such as size, position, colour or branding [50,64,70,76].…”
Section: Research Scopementioning
confidence: 99%
“…Based on mean acceptability scores, the majority of HWLs (aside from image-and-text HWLs without calorie information) had a score higher than four (out of seven), which indicates participants viewed them as somewhat acceptable. Another recent study demonstrated similar acceptability ratings for image-and-text HWLs ( Pechey et al, 2020 ). Due to the higher acceptability for text-only HWLs, and evidence of their effectiveness, it may be that HWLs in text form are the most promising labels for initial implementation.…”
Section: Discussionmentioning
confidence: 68%
“…annoyance at or deliberately not engaging with the HWL) ( Maynard et al, 2014 ; McCloud, Okechukwu, Sorensen, & Viswanath, 2017 ), although these behaviours do not necessarily interfere with quitting behaviours ( Brewer et al, 2019 ; Cho et al, 2016 ). HWLs placed on alcoholic beverages that include shocking or explicit pictures are rated as more effective than those with less severe pictures ( Maynard, Gove, Skinner, & Munafò, 2018 ), but have been shown to increase reactance and avoidance behaviours ( Sillero-Rejon et al, 2018 ) and may be less acceptable ( Clarke et al, 2020b ; Pechey et al, 2020 ). Initial studies suggest that text-only HWLs on SSBs ( Roberto, Wong, Musicus, & Hammond, 2016 ) and image-and-text HWLs on energy-dense snacks are generally accepted ( Pechey et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation